693 views
4 votes
Rewrite the function by completing the square. f(x)=x^{2}+2x+26

User Firecall
by
4.9k points

1 Answer

2 votes

Answer:

x = 4 + √3 and x = 4 − √3

Explanation:

(a−b)^2=a^2−2ab+b2

a^2−b^2=(a−b)(a+b)

−2x^2+16x−26

=−2(1x^2−8x+13)

=−2(x^2−8x+13+3−3)

=−2(x^2−8x+16−3)

=−2(x^2−2(4)x+4^2−3)

=−2((x−4)^2−3)

=−2((x−4)^2−(√3)^2)

=−2((x−4)−√3)((x−4)+√3)

=−2((x−(4+√3)((x−(4−√3))

The zeros of the given algebraic expression are:

−2x^2+16x−26=0

−2((x−(4+√3)((x−(4−√3))=0

x = 4 + √3 and x = 4 − √3

I strongly suggest using the quadratic formula as this problem is much easier to solve using it.

x = (−b ±
\sqrt{b^(2)-4ac } ) / 2

User Jlhonora
by
4.7k points